The role of chest CT in deciphering interstitial lung involvement: systemic sclerosis versus COVID-19. (28th July 2021) - Orlandi, Martina; Landini, Nicholas; Sambataro, Gianluca; Nardi, Cosimo; Tofani, Lorenzo; Bruni, Cosimo; Bellando-Randone, Silvia; Blagojevic, Jelena; Melchiorre, Daniela; Hughes, Michael; Denton, Christopher P; Luppi, Fabrizio; et al.
Abstract: Objective: The aim of this study was to identify the main CT features that may help in distinguishing a progression of interstitial lung disease (ILD) secondary to SSc from COVID-19 pneumonia. Methods: This multicentric study included 22 international readers grouped into a radiologist group (RADs) and a non-radiologist group (nRADs). A total of 99 patients, 52 with COVID-19 and 47 with SSc-ILD, were included in the study. Results: Fibrosis inside focal ground-glass opacities (GGOs) in the upper lobes; fibrosis in the lower lobe GGOs; reticulations in lower lobes (especially if bilateral and symmetrical or associated with signs of fibrosis) were the CT features most frequently associated with SSc-ILD. The CT features most frequently associated with COVID- 19 pneumonia were: consolidation (CONS) in the lower lobes, CONS with peripheral (both central/peripheral or patchy distributions), anterior and posterior CONS and rounded-shaped GGOs in the lower lobes. After multivariate analysis, the presence of CONs in the lower lobes ( P < 0.0001) and signs of fibrosis in GGOs in the lower lobes ( P < 0.0001) remained independently associated with COVID-19 pneumonia and SSc-ILD, respectively. A predictive score was created that was positively associated with COVID-19 diagnosis (96.1% sensitivity and 83.3% specificity). Conclusion: CT diagnosis differentiating between COVID-19 pneumonia and SSc-ILD is possible through a combination of the proposed score and radiologic expertise. The presence of consolidation in the lower lobes may suggest COVID-19 pneumonia, while the presence of fibrosis inside GGOs may indicate SSc-ILD.